Genome-wide characterization of histone deacetylases in Fusarium proliferatum: phylogeny, structure, and stress responses - Shi, Hong-Mei; Liao, Hong-Xin; Wen, Jin-Rui; Cun, Huan-Qi; Hong, Yun-Ju; Hu, Zhang-Feng; Xu, Fu-Rong; Noiprasert, Sulukkana; Apiwongsrichai, Kanyaphat; Liu, Xiao-Yun; Dong, Xian (Frontiers in Microbiology, 2026)
BackgroundFusarium proliferatum, a globally distributed phytopathogen causing destructive root rot in economically vital crops, employs epigenetic mechanisms to adapt to environmental conditions.ResultsOur genome-wide characterization identified eight histone deacetylase (FpHDACs) genes phylogenetically classified into RPD3/HDA1 and Sirtuin subfamilies. Comprehensive genomic characterization revealed two distinctive features: expanded domain architectures exemplified by the Arb2domain within Fp_HDA1, and subcellular localization prediction indicates—where most FpHDACs reside cytoplasmically under neutral pH, but undergo nuclear translocation in alkaline environments. Evolutionary diversification occurred principally via subfunctionalization rather than gene duplication, evidenced by non-clustered chromosomal distribution (8 genes across 5 chromosomes), divergent gene architectures in intron-exon organization and CDS lengths, and promoter cis-element enrichment featuring combinatorial stress-responsive signatures, most notably the dehydration-responsive DRE motifs exclusive to Fp_HOS3. Expression profiling analysis reveals a conserved global suppression of FpHDACs under abiotic stress, which is markedly potentiated by histone deacetylase inhibitor treatment. Crucially, the observed suppression was counterbalanced by a context-dependent induction of Fp_HOS3—specifically triggered under oxidative and cell wall stress, but not by other stressors. This specialized isoform functions as a compensatory epigenetic modulator, fine-tuning stress responses through targeted histone modification.ConclusionThis study provides the first systematic elucidation of the HDAC gene family’s core structural and functional characteristics in F. proliferatum, yielding novel insights into the adaptive strategies—both conserved and innovative—that underpin fungal stress epigenetics.